ANALYSIS OF WRITING PROBLEMS IKIP SILIWANGI STUDENTS - Yusep Ahmadi F; Diena San Fauziya; Aurelia Saktiyani (IKIP Siliwangi, 2019)
This research is research that focuses on analyzing the ability to write a paper by IKIP Siliwangi students. The purpose of this research problem is how to write scientific papers of IKIP Siliwangi students and what aspects are weaknesses in the scientific works of IKIP Siliwangi students. This research method is a descriptive qualitative method. The data sample consisted of 33 scientific papers of Indonesian Language Education Study Program students. The data analysis technique is by assessing papers using basic instruments, each student paper will get a maximum score of 100. The results of the research are then described to get a clear and correct description. The results showed that the average score of student papers was 53.9. This value is categorized as less. The weakness aspects of student papers lie in 1. Conventions of the paper relating to the consistency of paragraph typography; 2. Aspects of content meaningfulness related to the logical content of the paper and supported by information and data; 3. Scientific aspects related to effective sentences, quotations, and bibliography. The results of this study can be summed up in two points. First, the weakness of the writing of the Siliwangi IKIP student papers is the result of the students' inaccuracy in paying attention to new papers and the typing process; Second, students still lack knowledge of grammar, various standard languages, and Indonesian spelling.Keywords: writing skills analysis, writing papers